A performance assessment of women in managerial positions in the Lepelle-Nkumbi Municipality, Limpopo Province - Thaba, Kgomotlokoa Linda (University of Limpopo (Turfloop Campus), 2007)
Numerous programmes addressing performance assessment in the workplace have been designed and implemented in various organizations. In South Africa, public institutions have employed various appraisal systems with mixed results. A new tool for performance assessment has been designed and implemented since 2003 (for the past three years). This tool is called Performance Management Development System (PMDS).This study is based on the performance assessment of women in managerial positions, in the Lepelle-Nkumpi Municipality, Capricorn District, Limpopo Province. It explores the views of women managers on the challenges they are faced with, the type of support they receive, the effects of PMDS on work performance and the extent of institutional intervention at workplace. The qualitative techniques were used on the population of 180 women managers. The sample size of 114 was selected using random sampling method. The findings indicate the need to improve Performance Management and Development Systems (PMDS) and Performance Instruments (PIs) in order to create an environment conducive to better performance standards of women managers.
Thesis (M.Dev.) --University of Limpopo, 2006
Keywords: Performance assessment; Women; Managerial positions; 658.3125; Women executives; Performance standards; Performance -- Management